How democracies prevail: democratic resilience as a two-stage process. Issue 5 (4th July 2021) - Boese, Vanessa A.; Edgell, Amanda B.; Hellmeier, Sebastian; Maerz, Seraphine F.; Lindberg, Staffan I.
ABSTRACT: This article introduces a novel conceptualization of democratic resilience - a two-stage process where democracies avoid democratic declines altogether or avert democratic breakdown given that such autocratization is ongoing. Drawing on the Episodes of Regime Transformation (ERT) dataset, we find that democracies have had a high level of resilience to onset of autocratization since 1900. Nevertheless, democratic resilience has become substantially weaker since the end of the Cold War. Fifty-nine episodes of sustained and substantial declines in democratic practices have occurred since 1993, leading to the unprecedented breakdown of 36 democratic regimes. Ominously, we find that once autocratization begins, only one in five democracies manage to avert breakdown. We also analyse which factors are associated with each stage of democratic resilience. The results suggest that democracies are more resilient when strong judicial constraints on the executive are present and democratic institutions were strong in the past. Conversely and adding nuance to the literature, economic development is only associated with resilience to onset of autocratization, not to resilience against breakdown once autocratization has begun.